Learning in Networks of Knowledge : Improving Student Outcomes Using Web 2.0 Concepts and a Knowledge-networking Approach. - Allen, Matthew (Australian Learning and Teaching Council (ALTC), 2011)
The Learning in Networks of Knowledge (LINK) Project explored and identified Web 2.0 applications and tools that can contribute to innovative and agile teaching and learning approaches centred on knowledge production in a networked environment. These approaches and a wide range of Web 2.0 applications were tested within an applied research setting in the Department of Internet Studies at Curtin University. Pedagogical challenges involved the development of authentic learning experiences and assessment tasks, while providing effective cognitive scaffolding within which learning could occur. The project website provides examples, guidance material, publications, tools and resources and should be read with the report.